Initial teaching of the concept of fraction by preservice Primary school teachers - Elena Castro Rodríguez; Luis Rico Romero; Pedro Gómez (Universidad de La Rioja, 2014)
In this paper we investigate about the pedagogical content knowledge that a group of preservice primary school teachers put into play when composing a text with which to start primary school students in the partwhole notion of fraction. To analyse the productions, we used a model of didactic analysis, through its content and instructional analysis categories. The results highlight the content of fractions that the participants selected, how they proposed to introduce this content and the uses of the representations made in their responses.